Shifted 1/N expansion for the Klein-Gordon equation with vector and scalar potentials - Mustafa, Omar; Sever, Ramazan (American Physical Society (APS), 1990)
The shifted 1/N expansion method has been extended to solve the Klein-Gordon equation with both scalar and vector potentials. The calculations are carried out to the third-order correction in the energy series. The analytical results are applied to a linear scalar potential to obtain the relativistic energy eigenvalues. Our numerical results are compared with those obtained by Gunion and Li
The file in this item is the publisher version (published version) of the article.
Keywords: Pshysics; Klein-Gordon equation